Sustaining Government Internal Auditor Performance: A Mixed Method Study - Teng Sauh Hwee; Siti Aisyah Nasution (JASF: Journal of Accounting and Strategic Finance, 2024)
Both public and private organizations in the modern era greatly value the services of auditors since the outcomes of their decisions can reveal an organizations transparency. To ensure no errors are made when evaluating an organization, an auditor needs to be competent and independent in attitude. This study aims to analyze and examine the factors that influence time budget pressure, independence, and competence on internal auditor performance in BPKP North Sumatera. Research is being conducted using an applied mixed-methods approach. All BPKP North Sumatera auditors are included in the research population for both the qualitative and quantitative sections. Purposive sampling was used to select six audit managers and staff for the qualitative section research sample and to select fifty-five people for the quantitative section study sample. The data was analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that time budget pressure, independence and competence have significant effects on the internal auditor performances. Meanwhile, motivation had no effect on the performance of the internal auditor in BPKP North Sumatra. Motivation is proven to be able to mediate the effect of independence on auditor performance. Motivation is unable to mediate the effect of time budget pressure and competence on the internal auditor performances in BPKP North Sumatera. The study findings suggest that internal auditors should be considered when evaluating government sector audits and that they should be provided with information to help government internal auditors maintain and enhance audit quality.